2003
DOI: 10.1186/1471-2342-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic findings and clinical implications of persistent primitive hypoglossal artery

Abstract: Background: The primitive hypoglossal artery (PHA) is a rare vascular anomaly, which belongs to the group of carotid-basilar anastomosis that may occur in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…A possible role for the hemodynamics at the level of the PCA´s branching off the ICA has been postulated in the past (13). Our investigation revealed that the incidence of PCA in patients undergoing ICA surgery is slightly and significantly higher than in those who underwent MRA from various reasons (3) (1.6% vs 0.6%, Binomial test).…”
Section: Discussionmentioning
confidence: 61%
“…A possible role for the hemodynamics at the level of the PCA´s branching off the ICA has been postulated in the past (13). Our investigation revealed that the incidence of PCA in patients undergoing ICA surgery is slightly and significantly higher than in those who underwent MRA from various reasons (3) (1.6% vs 0.6%, Binomial test).…”
Section: Discussionmentioning
confidence: 61%
“…As the posterior communicating arteries develop later in gestation, these vessels typically regress. Embryologically, the otic artery typically regresses at approximately 4 weeks of gestation, followed by the hypoglossal and trigeminal arteries, then finally the proatlantal intersegmental artery at 7–8 weeks, when the vertebral arteries are fully developed 1 2…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the group of segmental arteries, which establish dorsoventral anastomoses during early fetal life (Vlychou et al 2003). Although these segmental arteries are normally obliterated after the 40th day, sporadically one remains patent resulting in a carotid-basilar anastomosis during adult life (Vlychou et al 2003).…”
Section: Hypoglossal Arterymentioning
confidence: 99%